To copy or not to copy: an evaluation of English undergraduate majors’ awareness of plagiarism - Lotfie, Maskanah Mohammad (2012)
The act of taking any written idea of another person and claiming that the idea is the result of one's own findings is a part of the definition of plagiarism. Plagiarism is a problem that is observed to be on the rise among students at the tertiary level and has grown with the advent of inexhaustible body of online resources. Plagiarism could be present in students’ academic writing in the form of extended pieces of perfect but blatantly copied work or in deceptively inconspicuous smaller portions of unattributed prose. Undergraduates, being young and at the early stage of exposure to the rules of the academia, may claim ignorance of what constitutes plagiarizing. With those issues in mind, this study has been administered to firstly evaluate students’ awareness of plagiarism. Secondly, it is an evaluation of the extent to which students’ work are similar to online resources.